HYDROGEN SULFIDE AND OTHER REDUCED FORMS OF SULFUR IN OXIC WATERS OF LAKE DORONINSKOE, EASTERN TRANSBAIKALIA - Zamana L.V.; Borzenko S.V. (My University, 2007)
Simultaneous occurrence of oxygen and hydrogen sulfide was established by hydrochemical investigations in the waters of the Black and Baltic seas at a depth of more than 50 m (c-layer). The most probable reason for the appearance of H2S and other sulfur species with intermediate oxidation states (thiosulfates and sulfites) is sulfate reduction in situ, i.e., immediately in the c-layer. A great number of publications have been devoted to the problem of the formation of hydrosulfuric, especially underground, mineral waters [6, 11, and others]. However, the presence of H2S in the oxic layer was reported only by few authors [8 and others], who believed that hydrogen sulfide can be supplied in part from bottom sediments. Data on other sulfur species (mainly, thiosulfates and sulfites) are rare. The formation of suboxidized sulfur species (thiosulfates and sulfites) in waters during the oxidation of sulfide deposits has been studied in more detail.